Multifunctional coatings of nickel-titanium implant toward promote osseointegration after operation of bone tumor and clinical application: a review - Du, Tianhao; Liu, Jia; Dong, Jinhan; Xie, Haoxu; Wang, Xiao; Yang, Xu; Yang, Yingxin (Frontiers in Bioengineering and Biotechnology, 2024)
Metal implants, especially Ni-Ti shape memory alloy (Ni-Ti SMA) implants, have increasingly become the first choice for fracture and massive bone defects after orthopedic bone tumor surgery. In this paper, the internal composition and shape memory properties of Ni-Ti shape memory alloy were studied. In addition, the effects of porous Ni-Ti SMA on osseointegration, and the effects of surface hydrophobicity and hydrophilicity on the osseointegration of Ni-Ti implants were also investigated. In addition, the effect of surface coating modification technology of Ni-Ti shape memory alloy on bone bonding was also studied. Several kinds of Ni-Ti alloy implants commonly used in orthopedic clinic and their advantages and disadvantages were introduced. The surface changes of Ni-Ti alloy implants promote bone fusion, enhance the adhesion of red blood cells and platelets, promote local tissue regeneration and fracture healing. In the field of orthopaedics, the use of Ni-Ti shape memory alloy implants significantly promoted clinical development. Due to the introduction of the coating, the osseointegration and biocompatibility of the implant surface have been enhanced, and the success rate of the implant has been greatly improved.